About the collection of the species of the genus Festuca L. (Poaceae) in the herbarium of the Institute of Ecology of the Carpathians of NAS of Ukraine (LWKS) - Беднарська, І. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
As a result of monograph studying of the Festuca genus taxonomy in the flora of Ukraine, Belarus and Lithuania, on the base of LWKS specialized herbarium collection of the genus has been created. The key peculiarity of the collection are population grounds as to gathering material. As of today about 550 population sample groups with 20–30 specimens in each have been stocked, which total approximately 11 thousands of plants. The collection represents diversity of populations (mostly narrow-leaved fescue species) in various geographical areas and allows analyzing peculiarities of species differentiations anatomically and morphologically in different ecological conditions, in natural and anthropogenically disturbed biotopes, in cultivation conditions and even in weather-climatic changes in different years.